Research progress in physiological effects of resistant substances of Urtica dioica L. on animal performance and feed conversion - Zhang, Yifan; Zhang, Xin; Zafar, Muhammad Hammad; Zhang, Jinying; Wang, Jiasheng; Yu, Xiang; Liu, Wujun; Wang, Mengzhi (Frontiers in Plant Science, 2023)
Animal feed as one of the main factors affecting animal growth and development. Due to the progressive increase in animal feed costs, there is an urgent need for low cost, high quality plant crops to be added to animal diets in order to reduce feed costs. The Urtica plant is an annual or perennial herb. It is rich in nutrients and has a high fibre content, of which Urtica dioica has a high reproductive and regenerative capacity, extensive coverage and high nutritional value. This review details the advantages of Urtica dioica as a replacement fodder in terms of its germplasm specificity, nutritional composition and fodder application status. Its roots, stems, leaves and seeds are of high medicinal, edible, textile and forage value. The active ingredients of each part were found to have anti-cancer effects through antioxidant effects and promotion of apoptosis of cancer cells. Under shade, Urtica dioica is highly adaptable, while under drought stress conditions it also reduces light absorption and ensures carbon assimilation through light energy conversion efficiency. It can therefore be added to animal diets as a suitable feed to reduce costs and improve economic efficiency. In this paper, the feasibility of using Urtica dioica as feed is investigated, and the progress of research and exploitation of Urtica dioica is systematically described.